The Role of Religious Centre in Monash University: Perspective of Three Indonesian Muslim Students - Aflahah, St (Religió Jurnal Studi Agama-agama, 2022)
This study aims to explore the perspective of three Indonesian Muslim students at Monash University concerning the availability of Religious Centre which facilitates some aspects of students’ spiritual inquiry. This study deals with the primary data through observation and semi-structured interviews as qualitative research. This research reveals that Religious Centre has a significant role in fulfilling students’ spiritual needs, including the prayer room for Muslim students, and also fosters students’ tolerance by putting prayer rooms for all religions in the same building. The university students found that Religious Centre is significant in preserving their religiosity and relieving them to perform prayers inside the campus. Likewise, it has eased students in managing academic challenges. In addition, this study found that Religious Centre has contributed to maintaining the religiosity of three Indonesian Muslim students: helping them cheering educational challenges and controlling their academic stresses.